All‐Aqueous‐Processed Injectable In Situ Forming Macroporous Silk Gel Scaffolds for Minimally Invasive Intracranial and Osteological Therapies. Issue 16 (16th June 2020) - Liu, Keyin; Fan, Zhen; Wang, Tianji; Gao, Zhiheng; Zhong, Junjie; Xiang, Geng; Lei, Wei; Shi, Zhifeng; Feng, Yafei; Mao, Ying; Tao, Tiger H.
Abstract: Hydrogels are widely utilized in regenerative medicine for drug delivery and tissue repair due to their superior biocompatibility and high similarity to the extracellular matrix. For minimally invasive therapies, in situ forming gel scaffolds are desirable, but technical challenges remain to be overcome to achieve the balance between tissue‐like strength and cell‐sized porosity, especially for intracranial and osteological therapies. Here, a new method—inspired by the liquid crystalline spinning process in natural silk fibers—is reported for preparing injectable silk gel scaffolds with favorable preclinical efficacy and unique characteristics including 1) in situ gelling for minimally invasive surgeries, 2) controllable porosity for efficient cellular infiltration and desirable degradation, 3) resilient and tunable mechanical properties that are compatible with the modulus regime of native soft tissues, and 4) all‐aqueous processing that avoids toxic solvents and enables facile loading of bioactive agents. Moreover, hierarchically structured heterogeneous silk gel scaffolds with variable porosity and bioactive agent gradients within 3D matrices can be achieved for sustained drug release and guided tissue regeneration. Preclinical efficacy studies in rodent models show efficient bacterium and glioma inhibition and positive effects on bone regeneration and vascularization. Abstract : A new method is reported for preparing injectable silk gel scaffolds inspired by the liquid crystalline spinning process in natural silk fibers, with controllable porosity and sufficient mechanical strength that can be used for minimally invasive intracranial and osteological therapies. Meanwhile, silk gel scaffolds with 3D spatial patterning of porous materials and bioactive agent gradients can be achieved.